Hydrogels and Their Role in Biosensing Applications. Issue 11 (3rd May 2021) - Herrmann, Anna; Haag, Rainer; Schedler, Uwe
Abstract: Hydrogels play an important role in the field of biomedical research and diagnostic medicine. They are emerging as a powerful tool in the context of bioanalytical assays and biosensing. In this context, this review gives an overview of different hydrogels and the role they adopt in a range of applications. Not only are hydrogels beneficial for the immobilization and embedding of biomolecules, but they are also used as responsive material, as wearable devices, or as functional material. In particular, the scientific and technical progress during the last decade is discussed. The newest hydrogel types, their synthesis, and many applications are presented. Advantages and performance improvements are described, along with their limitations. Abstract : To achieve a good biosensing performance it is of great importance how the bioprobes are immobilized on the substrate and how well they are accessible. In that regard, hydrogels can provide several additional features to the performance of a biosensor. Beneficial characteristics include their solution‐like behavior and their ability to function as a visual indicator of target detection.